Siddhantik Vivechhan of Amlapitta – A Review - Radhika, Sahu Hrishikesh; Dipali, Swami (International Research Journal of Ayurveda & Yoga, 2022)
Ayurveda is one among the oldest health science. Nowadays due to faulty life style, diet pattern mental stress and strain healthy status of human being is in declining. Due to changing life style, there is tremendous increase in disorder related to mahasrotas (gastrointestinal tract). Amlapitta is one of the major diseases which occur in mahasrotas. Amlapitta is pitta predominance disease which is related to Annavaha srotas & Purishvaha Srotas occurs due to mandagni and ama. When Amla guna of pitta is increased is called Amlapitta. Various acharyas has explained amlapitta as separate disorders but Samprapti of Amlapitta is clearly mentioned in Grahani chikitsadhyay while describing samprapti of Grahani Dosha. The basic principle of treatment is mainly nidana parivarjana, shodhana, and shamana chikitsa. Vamana and Virechana are mentioned for urdhva gati and adho gati of doshas.